HDAC9 structural variants disrupting TWIST1 transcriptional regulation lead to craniofacial and limb malformations - Hirsch, Naama; Dahan, Idit; D'haene, Eva; Avni, Matan; Vergult, Sarah; Vidal-García, Marta; Magini, Pamela; Graziano, Claudio; Severi, Giulia; Bonora, Elena; Nardone, Anna Maria; Brancati, Francesco; et al. (Genome Research, 2022)
Structural variants (SVs) can affect protein-coding sequences as well as gene regulatory elements. However, SVs disrupting protein-coding sequences that also function as cis-regulatory elements remain largely uncharacterized. Here, we show that craniosynostosis patients with SVs containing the histone deacetylase 9 (HDAC9) protein-coding sequence are associated with disruption of TWIST1 regulatory elements that reside within the HDAC9 sequence. Based on SVs within the HDAC9‐TWIST1 locus, we defined the 3′-HDAC9 sequence as a critical TWIST1 regulatory region, encompassing craniofacial TWIST1 enhancers and CTCF sites. Deletions of either Twist1 enhancers (eTw5-7Δ/Δ) or CTCF site (CTCF-5Δ/Δ) within the Hdac9 protein-coding sequence led to decreased Twist1 expression and altered anterior/posterior limb expression patterns of SHH pathway genes. This decreased Twist1 expression results in a smaller sized and asymmetric skull and polydactyly that resembles Twist1+/− mouse phenotype. Chromatin conformation analysis revealed that the Twist1 promoter interacts with Hdac9 sequences that encompass Twist1 enhancers and a CTCF site, and that interactions depended on the presence of both regulatory regions. Finally, a large inversion of the entire Hdac9 sequence (Hdac9INV/+) in mice that does not disrupt Hdac9 expression but repositions Twist1 regulatory elements showed decreased Twist1 expression and led to a craniosynostosis-like phenotype and polydactyly. Thus, our study elucidates essential components of TWIST1 transcriptional machinery that reside within the HDAC9 sequence. It suggests that SVs encompassing protein-coding sequences could lead to a phenotype that is not attributed to its protein function but rather to a disruption of the transcriptional regulation of a nearby gene.
10.1101/gr.276196.121